Ensino-aprendizagem de análise combinatória no ensino médio: sequência didática pautada na resolução de problemas - Eldeson Inácio da Costa da Silva (2021)
The teaching of Combinatorial Analysis is of fundamental importance for the mathematical and citizen formations of the students, arousing them for exemplary forms of organizing and structuring their reasoning and preparing them to enter into the labor market, in addition to enabling better understanding dealing with an increasingly complex technical-scientific-scientific society. However, what has been perceived is that this teaching has not taken advantage of the potential of the matter, often summarizing the direct explanation of its techniques and procedures and the exaggerated use of meaningless formulas. This work then proposes a didactic sequence for teaching-learning Combinatorics in high school, structured in problem-solving. It is the result of a bibliographic research, held in order to deepen the understanding of the teaching-learning process of Combinatorics, the problem-solving methodology and the structuring of didactic sequences. The problem-solving methodology adopted consists of the combination of the methods of Onuchic et al. (2019) and Polya (1995), emerging the didactic sequence from its application to the development of Combinatorics topics contemplated in high school. The results are discussions and relevant conclusions about Combinatorics teaching-learning, in addition to the structuring of an alternative and constructive step by step for the development of this process, from the problem solving. It is a material full of discussions and considerations conducive to awaken reflections on mathematics teaching in general, reflecting on how it has been structured and how with it contributing